The concept of custody in Islamic law - Zahraa, Mahdi; Abd Malek, Normi (Brill Academic Publisher, 1998)
What is the role of women in the Islamic institution of custody? This article will examine these issues based on the views of classical jurists as well as contemporary scholars.